Improving English Speaking Skills Of Youth In Sei Tualang Labura Through Interactive Learning Methods - Zainuddin; Gumarpi Rahis Pasaribu (Rahis Cendekia Indonesia, 2024)
This community service initiative aimed to enhance the English speaking proficiency of youth in Sei Tualang, Labuhanbatu Utara, through the implementation of interactive learning methods. The background of this program lies in the limited exposure and opportunities for rural youth to practice English communicatively, resulting in low confidence, limited vocabulary, and anxiety in speaking. To address this gap, the program designed a four-week interactive learning workshop that utilized student-centered methods such as role-playing, vocabulary games, storytelling, peer discussions, and real-life conversation simulations. The implementation involved both instructional delivery and motivational strategies to create a non-threatening, supportive learning atmosphere. The participants, aged between 13 and 18 years, were actively involved in communicative tasks that gradually increased in complexity. Pre- and post-activity observations and facilitator journals indicated a noticeable improvement in fluency, vocabulary range, pronunciation accuracy, and confidence. Participants demonstrated a higher willingness to communicate in English and showed a growing ability to sustain short conversations on familiar topics. Beyond linguistic outcomes, the program also fostered teamwork, critical thinking, and self-expression among the learners. Despite challenges such as limited access to technological tools and English materials, the creative adaptation of activities to suit the local context ensured the success of the program. This community engagement highlights that interactive and contextualized learning methods can serve as an effective approach to address the language learning needs of youth in under-resourced areas.